Soy isoflavone supplementation increases equol-producing capability in postmenopausal women with osteopenia - Elly Herwana; Rianto Setiabudy; Sidartawan Soegondo; Ali Baziad; Adi Hidayat (Universa Medicina, 2012)
Background Isoflavone containing soy protein has been associated with beneficial health effects. Equol, a gut bacterial metabolite of the isoflavone daidzein, has been hypothesized to be the cause of the effectiveness of isoflavones. The objective of this study was to evaluate the effect of 100 mg/day soy isoflavone supplementation for 3 months on the ability to produce equol in postmenopausal women with osteopenia.MethodA pre-post experimental study was conducted to assess the effects of 100 mg/day soy isoflavone supplementation on equol production capability and the proportion of equol producers to non-equol producers in postmenopausal women with osteopenia. A total of 39 subjects received 1 supplement tablet containing 100 mg soy isoflavones (genistein, daidzein) for 3 months. Determination of serum genistein, daidzein, and equol concentrations was performed twice at baseline and at 3 months post-supplementation using high-performance liquid chromatography mass spectrophotometry (HPLC-MS). Equol producer status was determined by the detection of a serum equol concentration of 5 µg/L.Results Mean genistein and daidzein concentrations at baseline were 86.2 ± 68.4 ìg/L and 16.7 ± 18.6 ìg/L, respectively. The proportion of equol producers was 69.2%. After 3 months of soy isoflavone supplementation the serum concentrations of genistein and daidzein significantly increased to 161.0 ± 5.8 ìg/L (p=0.000) and 49.9 ± 40.4 ìg/L (p=0.000), respectively, and the proportion of equol producers also significantly increased (100.0%).ConclusionSoy isoflavone supplementation was capable of increasing the serum concentrations of isoflavones (genistein and daidzein) and the equol-producing capacity of postmenopausal women with osteopenia.